(untitled) (مجلة المنصور, 2022)
The research aims to formulate an applied vision on how the relationship between managers’ practices and the holistic marketing dimensions of the objectives of the organization and its partners. A sample of (three) companies was selected by the Ministry of Construction, Housing. The sample was surveyed with (144) members of these companies, divided into several administrative levels (manager, engineer, administrative). A number of hypotheses have tested for correlation and influence among search variables. A number of measures have used to verify the hypotheses, including the questionnaire as a main tool for collecting data and information, consisting of( 60) items covering research aspects (managers’ practices, holistic marketing dimensions) And personal interviews, personal observation of the researcher and using a variety of statistical tools to analyze and process data and information using the program(SPSS vr23). The research found a number of conclusions, the most important of which are:( The direction of the managers of the companies investigated about the accounting practices of different types and less of the other practices, the possibility of directing the construction companies in question to build relationships with the stakeholders. , Adopt the method of recycling employees to establish cases of excellence and secure knowledge programs).